GENOME-WIDE ASSOCIATION STUDY OF A HEALTHY METABOLIC PHENOTYPE IN THE LONG LIFE FAMILY STUDY. (11th November 2018) - Marron, M; Miljkovic, I; Wojczynski, M; Boudreau, R; Christensen, K; Thyagarajan, B; Zmuda, J; Newman, A
Abstract: Familial longevity has been shown to be associated with healthy metabolic characteristics. We sought to develop a healthy metabolic phenotype in the Long Life Family Study to identify potential genes regulating metabolic health. The Long Life Family Study is a multi-center cohort of two-generation families selected for familial longevity. Using information from participants in the offspring generation, we developed a healthy metabolic phenotype by applying a Latent Profile Analysis to age- and gender-adjusted z-scores of body mass index, waist circumference, and fasting serum levels of glucose, insulin, triglycerides, high-density lipoprotein cholesterol, interleukin-6, and C-reactive protein. A subset of offspring-generation participants were defined as meeting the healthy metabolic phenotype if the Latent Profile Analysis classified them into a subgroup with a healthier profile of metabolic markers than expected given their age and gender, relative to the entire Long Life Family Study offspring generation. The log odds of meeting the healthy metabolic phenotype was used to calculate heritability and to apply a genome-wide association study. Among 1987 participants in the offspring generation (43% men; mean (standard deviation) age and body mass index: 60 (8) years and 28 ± 5 kg/m2), 388 (20%) met the healthy metabolic phenotype. The log odds of meeting the healthy metabolic phenotype was heritable (h2=0.40, p<0.001), with suggestive associations (p≤8.7E-07) detected near genes: LOC101927936, PRSS23, ZPR1, LOC105372224, and LOC105377365 (on 11p15.4, 11q14.2, 11q23.3, 18q23, and 4q25, respectively). Further investigation may indicate biologic pathways influencing metabolic health and longevity in the Long Life Family Study cohort.